Indeks Kesehatan Mental Menurut Rasulullah Saw.: Studi Takhrij dan Syarah Hadis dengan Pendekatan Psikologis - Zahra Yasmin; Wahyudin Darmalaksana; Ecep Ismail (UIN Sunan Gunung Djati Bandung, 2022)
This study aims to examine the hadith regarding mental health and its indicators according to the perspective of the Prophet Muhammad. This study uses a qualitative approach with takhrij and syarah hadith methods by applying contemporary analysis in the field of psychology. The results of the research and discussion reveal that the quality of the hadith is related to mental health with hasan li ghairihi status in terms of takhrij so that it can be accepted and used as a reference or argument for practicing Islam. Meanwhile, in terms of syarah hadith, mental health is one of the important things in the implementation of worship and in socializing. The conclusion of this research is the hadith narrated by Ibn Majah No. 2132 has a maqbul degree for efforts to maintain mental health from a psychological perspective, although in terms of rehabilitation or mental healing due to disorders it still needs to be investigated further.